1985
DOI: 10.1002/jat.2550050615
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of aromatic disulphides. III. In vivo haemolytic activity of aromatic disulphides

Abstract: Diphenyl disulphide, 4,4'-diaminodiphenyl disulphide, 2,2'-diaminodiphenyl disulphide, 4,4'-dimethyldiphenyl disulphide and 4,4'-dinitrodiphenyl disulphide, when administered orally to rats, induced haematological and pathological changes indicative of erythrocyte destruction in vivo. No evidence of haemolysis was detected, however, in animals receiving diphenyl disulphide-2,2'-dicarboxylic acid or dibenzyl disulphide. The order of activity of the various aromatic disulphides in provoking in vivo haemolysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…It has been reported that aromatic disulfides induce hemolysis of erythrocytes, 19,20 and in fact, diphenyl disulfide itself also exhibited significant hemolytic activity in this study. This compound induces hemolysis as the result of biological effects in erythrocytes such as hydrogen FIGURE 4.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…It has been reported that aromatic disulfides induce hemolysis of erythrocytes, 19,20 and in fact, diphenyl disulfide itself also exhibited significant hemolytic activity in this study. This compound induces hemolysis as the result of biological effects in erythrocytes such as hydrogen FIGURE 4.…”
Section: Discussionsupporting
confidence: 57%
“…The 23 chemicals listed in Table I were selected as candidate hemolytic compounds according to previous reports, [18][19][20] and the hemolytic behavior against rabbit RBCs was estimated using a simple survey method. As shown in Table I, although most of the compounds did not exhibit hemolytic activity under the conditions used in this study, Genapol X-080 and diphenyl disulfide significantly induced hemolysis.…”
Section: Hemolytic Activity Of a Candidate Compoundmentioning
confidence: 99%
“…All pH measurements were carried out on a Model pHS-3C pH meter (Shanghai, China). The probe PBO was characterized by 1 H NMR, 13 C NMR, IR and HRMS ( Fig. S12-14 in ESI †).…”
Section: Materials and Instrumentationmentioning
confidence: 99%
“…in CH 3 CN-PBS (10 mM, pH ¼ 7. dinitrophenyl ether and chemical-reaction-induced skeletal rearrangement would be happened. In addition, the product of the reaction of probe PBO with thiophenol was isolated by column chromatography, and further conrmed by 1 H NMR, 13 C NMR, high resolution mass spectrometry analysis ( Fig. S15-17 in ESI †).…”
Section: Mechanismmentioning
confidence: 99%
See 1 more Smart Citation